Diet and risk of endometriosis in a population-based case–control study - Trabert, Britton (2010)
Diet plausibly has a role in the aetiology of endometriosis through effects on steroid hormone levels; however, few published studies have examined the diet and endometriosis risk. We evaluated dietary risk factors for endometriosis in a population-based case–control study. Cases were 284 Group Health (GH) enrollees aged 18–49 years with newly diagnosed, surgically confirmed endometriosis between 1996 and 2001. Controls were 660 randomly selected age-matched female GH enrollees without a history of endometriosis. Nutrients and selected food groups were assessed using the Women’s Health Initiative FFQ. OR of endometriosis risk associated with dietary exposures were estimated using unconditional logistic regression and adjusted for identified covariates. Increased total fat consumption was associated with decreased endometriosis risk (fourth quartile v. lowest: OR 0·5, 95% CI 0·2, 1·0, P-trend=0·12). Increased β-carotene consumption and servings/d of fruit were associated with increased risk (β-carotene third quartile v. lowest: OR 1·7, 95% CI 1·1, 2·6; fourth quartile v. lowest: OR 1·6, 95% CI 1·0, 2·5, P-trend 0·16; fruit >2 servings/d v. <1: OR 1·5, 95% CI 1·0, 2·3, P -trend=0·04). We also found a suggestion of decreased endometriosis risk associated with the consumption of dairy products (2 servings/d v. ≤1: OR 0·6, >2 servings/d v. ≤1: OR 0·7), but this association was not statistically significant for the highest tertile. The present study suggests that specific dietary components may be associated with endometriosis risk.